The Implementation of Role Playing Model in Improving Students’ Understanding of Fardhu Kifayah at Grade XI of SMK Yaspi Labuhan Deli - Aryani, Fazra (Yayasan Rahmat Islamiyah, 2025)
This study aims to examine the implementation of the Role Playing learning model in improving students’ understanding of Fardhu Kifayah at Grade XI of SMK Yaspi Labuhan Deli. The background of this research is the low level of students’ comprehension regarding collective worship practices such as Fardhu Kifayah. The research method employed was Classroom Action Research (CAR) conducted in two cycles. The subjects of the study were students of Grade XI at SMK Yaspi Labuhan Deli. The instruments used included comprehension tests, observations, and documentation. The findings revealed that the application of the Role Playing model improved students’ understanding of Fardhu Kifayah, as indicated by the increase in test scores and students’ learning activities from cycle I to cycle II. Therefore, it can be concluded that the Role Playing model is effective in enhancing students’ understanding of Fardhu Kifayah material.